József Wohlmuth as School Inspector in the Pannonhalma Saint Benedict Order (Training and Practice : Journal of Educational Sciences, 2007)
The Hungarian Saint Benedict Order’s Monastery of Pannonhalma has been preserving our nation’s culture and also serving the spiritual needs of Hungarian Catholics for over a thousand year. The first church school was established in Pannonhalma in 996. This foundation of the monastery was instrumental in the development of society. The orders achieved favourable results in teacher training, such as elementary school education and secondary teaching. The author in his study examines an important period of the Catholic public schools’ supervision and control system of Pannonhalma Saint Benedict Order between the two World Wars. Between 1922 and 1931 József Wolmuth worked as primary education school inspector, and introduced significant changes. Not only had he monitored, but also helped the work of teachers. He established the Organization of Teachers of Pannonhalma Saint Benedict Order, which had a great impact on the professional development of teachers, the fast information changes between the schools and the governance, and the democratization of the control of public education.